Not just a spatial context: Understanding the extent of transport-related social exclusion / Mohd Afzan Mohamed, Asmah Alia Mohamad Bohari and Rusdi Rusli - Mohamed, Mohd Afzan; Mohamad Bohari, Asmah Alia; Rusli, Rusdi (2022)
Mobility and accessibility limitations because of transport-related issues influence the ability of individuals to participate in activities. People affected by this circumstance are referred to as "transport disadvantaged," which might eventually lead to their social exclusion. Various scholars have investigated transport-related social exclusion (TRSE) issues and revealed the common transport difficulties encountered, affecting individuals from multiple backgrounds. Extensive studies have been done by looking at specific measures, such as issues related to time and spatial aspects when analysing the accessibility level in a particular locality. These studies focused on public transport performance to justify the accessibility level and the individuals' accessibility level in a local area. Despite numerous attempts to tackle the TRSE issues, any study investigating individuals' ability to participate in activities would not be compelling unless the TRSE issues were examined from a broader perspective. This paper discusses reliable evidence from previous research on the TRSE categories. These researchers use these categories correspondingly to explain the causes of transport difficulties. Furthermore, over 50 peer-reviewed papers supporting these categories tying the discourse to transport mobility and accessibility restrictions were critically analysed. The findings provide insights to expand the understanding of the broad TRSE dimensions that would benefit future research investigating TRSE issues. The findings will also benefit the policymakers, designers, and users to understand more the importance of TRSE for better sustainable future development.